Surgical treatment of unicentric plasma cell histological type Castleman's disease - Marić Nebojša; Stanić Vojkan; Cvijanović Vlado; Ristanović Aleksandar; Kovačević Snežana; Krivokapić Žarko; Tasić-Radić Olga (Vojnosanitetski Pregled)
Introduction. Castleman’s disease or angiofollicular lymph hyperplasia is a rare disease with two identified clinical forms. Unicentric or localized form is characterized by isolated growth of lymph nodes, most often in mediastinum, and multicentric form is expressed as systemic disease with spread lymphadenopathy, organomegaly and presence of general symptoms of the disease. Histological types are hyalovascular, plasma-cell and transitive (mixed) cell. Case report. This case report shows a woman, 59 years old, with unicentric form of plasma-cell type of Castleman’s disease. Unicentric form is usually shown as hyalovascular histological type, extremely rare as plasma-cell type, and transitive (mixed) cell type was never described in literature as localized clinical form. The disease was manifested with chest pain, loss of body weight, exhaustion and weakness of legs. Further diagnostic procedures found the presence of enlarged lymph nodes paratracheally right, in a close contact with vena cava superior. The disease was confirmed by histopathological analysis of bioptated mediastinal lymph node after mediastinoscopy. Surgical treatment included extirpation of enlarged lymph nodes. After the regular postoperative condition, a full therapy effect was confirmed. Conclusion. Unicentric form of Castleman’s disease is expressed with enlarged lymph nodes on predilected places, usually in mediastinum. Surgical treatment is best method for the management of the disease and brings a full recovery of patient.